Implementasi Pemidanaan Judi Online Berdasarkan Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik Pertanggungjawaban Pidana Terhadap Pelaku Perjudian Online: Studi Putusan Nomor: 628/PID.B/2023/PN Sleman - Bernardus Alessandro Imantaka; Rehnalemken Ginting (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses criminal liability for perpetrators of online gambling crimes based on Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE Law) from the perspective of Indonesian criminal law. The research employs a normative juridical approach with a case study method on Decision Number 628/PID.B/2023/PN Sleman. The defendant was proven to have knowingly distributed and disseminated links to online gambling sites via social media, as well as obtained financial gain from these activities. Based on the judge’s decision, the defendant was sentenced to 1 year and 8 months in prison and fined IDR 250,000,000. The results indicate that the application of Article 27 paragraph (2) in conjunction with Article 45 paragraph (2) of the ITE Law is in accordance with the principles of criminal liability, including the elements of fault (mens rea) and unlawful acts (actus reus). Nevertheless, challenges remain in law enforcement against online gambling, particularly regarding sites operating abroad and the low level of public legal awareness. The recommendations provided include a more comprehensive legal approach to enhance the effectiveness of combating online gambling in Indonesia.